ASSESSING THE CANOPY INTEGRITY USING CANOPY DIGITAL IMAGES IN SEMIDECIDUOUS FOREST FRAGMENT IN SÃO CARLOS - SP- BRAZIL1 - Yamada,Thiago (2017)
ABSTRACT It is well-known that conducting experimental research aiming the characterization of canopy structure of forests can be a difficult and costly task and, generally, requires an expert to extract, in loco, relevant information. Aiming at easing studies related to canopy structures, several techniques have been proposed in the literature and, among them, various are based on canopy digital image analysis. The research work described in this paper empirically compares two techniques that measure the integrity of the canopy structure of a forest fragment; one of them is based on central parts of canopy cover images and, the other, on canopy closure images. For the experiments, 22 central parts of canopy cover images and 22 canopy closure images were used. The images were captured along two transects: T1 (located in the conserved area) and T2 (located in the naturally disturbance area). The canopy digital images were computationally processed and analyzed using the MATLAB platform for the canopy cover images and the Gap Light Analyzer (GLA), for the canopy closure images. The results obtained using these two techniques showed that canopy cover images and, among the employed algorithms, the Jseg, characterize the canopy integrity best. It is worth mentioning that part of the analysis can be automatically conducted, as a quick and precise process, with low material costs involved.